Association between olfaction and higher cortical functions in Alzheimer's disease, mild cognitive impairment, and healthy older adults. Issue 7 (9th August 2017) - Ward, Amanda M.; Calamia, Matthew; Thiemann, Erin; Dunlap, Jamie; Tranel, Daniel
ABSTRACT: Introduction : Neural regions important for smell are proximal and closely connected to cortical areas that have been strongly implicated in higher order functions of value-based decision making and emotional memory. The integrity of these neural regions are affected in aging and neurodegenerative conditions. Two specific predictions follow from these neuroanatomical arrangements—namely, that olfaction would be associated with value-based decision making and with emotional memory. Method : To test these predictions, we measured these different capacities in participants with presumed varying degrees of integrity of the relevant brain structures: specifically, 13 patients with Alzheimer's disease, 8 patients with mild cognitive impairment, and 20 healthy older adults. The participants completed detailed tests of olfaction, value-based decision making, emotional memory, and general cognitive ability. Results : Olfactory functioning was significantly associated with emotional and nonemotional memory. The association was especially strong and consistent for memory recall with olfaction, explaining as much as 10% additional variance over and above general cognition. Olfactory functioning was not strongly or consistently associated with decision making over and above general cognition. Conclusion : Olfaction is a strong predictor of memory recall. These findings may contribute to a better understanding of olfaction and specific cognitive domains known to be affected by aging and implicated in neurodegenerative disease.